Anxiety of Practice Teachers on Final Teaching Demonstration - Ira Gem Albasin-Lacaba; Medeliza Avenir; Jolina Permejo; Eduardo Edu Jr. Cornillez (Camarines Sur Polytechnic Colleges, 2022)
No studies have been conducted yet that focus on assessing students' anxiety levels during their final teaching demonstration. The study specifically aimed to identify the profile of the practice-teachers and determine their level of anxiety towards final teaching demonstrations, particularly in the areas of lesson planning, class management, and evaluation, leading to the proposal of interventions to manage their anxiety. A descriptive survey research design was utilized in this study. There were a total of 34 respondents, who were teacher education students at the Eastern Visayas State University-Tanauan Campus, Philippines, practicing as pre-service teachers in the second semester of the academic year 2019-2020. They were chosen using a total enumeration sampling design. The instrument used was adapted from The Student Teacher Anxiety Scale (STAS) by Hart (1987). The findings of the study revealed that generally, the student teachers experienced a normal level of anxiety for lesson planning during their final teaching demonstration. However, there is a need for them to improve their knowledge about the application of different teaching strategies. The student teachers also feel the same normal level of anxiety when it comes to class management. And lastly, they experienced an acceptable level of anxiety about being evaluated, although they tend to be very anxious about whether their performance will be accepted by their respective evaluators. The researchers recommend more training workshops about lesson planning for the students and letting them practice more teaching demonstrations to help manage their anxiety during their final teaching demonstration.